Design and synthesis of a folate-receptor targeted diazepine-ring-opened pyrrolobenzodiazepine prodrug conjugate. Issue 7 (1st April 2020) - Vlahov, Iontcho R.; Qi, Longwu; Santhapuram, Hari Krishna R.; Felten, Albert; Parham, Garth L.; Zou, Ning; Wang, Kevin; You, Fei; Vaughn, Jeremy F.; Hahn, Spencer J.; Klein, Hanna F.; Kleindl, Paul J.; et al.
Graphical abstract: Abstract: Pyrrolobenzodiazepines (PBDs) and their dimers (bis-PBDs) have emerged as some of the most potent chemotherapeutic compounds and are currently under development as novel payloads in antibody-drug conjugates (ADCs). However, when used as stand-alone therapeutics or as warheads for small molecule drug conjugates (SMDCs), dose-limiting toxicities are often observed. As an elegant solution to this inherent problem, we designed and synthesized a diazepine-ring-opened bis-PBD prodrug (pro-PBD-PBD) folate conjugate lacking the one of the two imine moieties found in the corresponding free bis-PBD. Upon entering a targeted cell, cleavage of the linker system, including the hydrolysis of an oxazolidine moiety, results in the formation of a reactive intermediate which possesses a newly formed aldehyde as well as an aromatic amine. A fast and spontaneous intramolecular ring-closing reaction subsequently takes place as the aromatic amine adds to the aldehyde with the loss of water to give the imine, and as a result, the diazepine ring, thereby delivering the bis-PBD to the targeted cell. The in vitro and in vivo activity of this conjugate has been evaluated on folate receptor positive KB cells. Sub-nanomolar activity with good specificity and high cure rates with minimal toxicity have been observed.